The Phenomenon of Speech Acts in The Sundanese Novel Istri-Istri Nu Dipihormat by Memen Durachman - Rahmah, Mega Sri; Ratnawati, Ratnawati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
This research is motivated by the importance of understanding the context of speech and speech acts to avoid misunderstanding in understanding speech. The source of the research data is the Sundanese novel Wife-wife nu Dipihormat by Memen Durachman because Sundanese novels have many messages about life and are one of the efforts to preserve the Sundanese language. The purpose of this research is to find out the speech acts in the dialogue of Memen Durachman's novel Wife-Wife nu Dipihormat through Austin's theory. The method used is the descriptive analytical method using data collection techniques in the form of literature review and data analysis. The results of the study show that of the 385 dialogues in the novel, the forms of speech acts found in this novel are locations with a total of 202 utterances, illocutionary acts with a total of 193 utterances, and perlocutions with a total of 228 utterances. The results of this study can be used as an alternative in paguneman learning that is by KIKD, so that it can be an effort to preserve Sundanese.